Art, truth and time essays in art - Scollard, Anselma (Edinburgh Luath Press, 2019)
Art, Truth and Time is a book which endeavours to show that artistic creation depends as much upon the body, as it does the soul, and the soul's intelligent use of the body's way of understanding. When there occurs a complete disjunction between the two, as occurs in much of contemporary art, art is stripped of its inherent beauty, its wholeness. In this book the author considers the nature of art from its earliest manifestations to the present day, endeavouring to show that its truth transcends time and place through the unity of soul and body and man's awareness of this unity, not a barren unity, but a unity which is profoundly creative.
Keywords: Art -- Philosophy; Art and religion; Art -- Psychology